Analysis of Air Pollution Migration during COVID-19 Lockdown in Krakow, Poland - Mateusz Zaręba; Tomasz Danek (Aerosol and Air Quality Research)
Abstract The historical analysis of particulate matter (PM) concentration proved that pro-clean-air legislation and grassroots movement have a positive impact on air quality in Krakow. However, when the temperature drops in late autumn, winter, and early spring, the problem of smog still occurs in the city. In a 24-hours averaging period, the concentration of PM10 has exceeded EU norms in 10 days in pandemic March 2021. It is estimated that 50% of the carbon fraction in PM10 measured in Krakow comes from domestic heating. This is mostly caused by the migration of air pollutants from neighboring municipalities (where the use of fossil fuels for heating is allowed) to Krakow (where this type of households heating is forbidden). In this paper, we analyzed PM10 concentrations in Krakow and neighboring municipalities. Moreover, we showed the main migration directions of air pollutants in connection with wind direction. We used statistical analysis to examine the relations between PM10 concentrations and other physical characteristics of the atmosphere. It includes measurements of pressure, temperature, and humidity. We were collecting data during early spring 2021 when car transportation was limited due to the COVID-19 lockdown in Poland. Car transportation in Krakow is responsible for up to 20% of the PM10 carbon fraction concentration. It allowed for observation of air pollutions from solid fuel heating with minimum traffic-generated pollution background. The Airly© low-cost sensors (LCS) network was used for this study.